Insight into Newtonian fluid flow and heat transfer in vertical microchannel subject to rhythmic membrane contraction due to pressure gradient and buoyancy forces. (March 2022) - Bhandari, D.S.; Tripathi, Dharmendra; Prakash, J.
Highlights: A heat transfer analysis with membrane pumping mechanism is presented. Viscous fluids flow in presence of buoyancy force is anlyzed. The effects of membrane on stream line patterns and isotherms are discussed. Thermal effects on membrane pumping mechanism are examined. Results will be applicable in thermo-controlled micropumping devices for diagnosis in health care. Abstract: The designing of the thermo-controlled micro pumping devices for diagnosis in health care and mixing of the samples at particular temperature are very much essential. Transient analysis for heat and mass transfer in a finite length vertical microchannel is presented in this article. This pumping model aims to analyze the streamlines and isotherms under various parameters at two different phases (contraction and relaxation) of membrane motion. The velocity fields under the effects of Grashof number and heat source parameter are also discussed to examine the velocity profile in the vertical microchannel. Considering the creeping nature of physiological transport phenomena, a lubrication approach has been employed. An analytical approache is adopted to derive the exact solutions, and finite difference method with in-house Matlab code are utilized to simulate the results and validate the anlytical results. Pressure is generated due to the kinematic of membrane motion and controlled by the thermal effects and buoyancy force. The contour of axial velocity enhanced by 28.32% as Grashof number changes from 0 to 2 and heat source parameter changes from 0 to 2 respectively. Volumetric flow rate also varies from 0.08 to 0.12 and 0 to 0.1 with change in Grashof number from 0 to 2 and heat source parameter from 0.01 to 4 respectively.